2020
DOI: 10.1002/osp4.395
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and intrapartum obstetric complications among pregnant women: Retrospective cohort analysis from medical birth registry in Northern Tanzania

Abstract: Background:In the last decade, Tanzania has observed a dramatic increase in over-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Simultaneously, obesity is also prevalent in low-and middle-income countries and high-income countries, particularly among economically poor populations (22)(23)(24)(25) . Maternal obesity is associated with serious adverse pregnancy outcomes including early pregnancy loss, preterm birth, stillbirth, gestational diabetes, pre-eclampsia and other hypertensive disorders, higher rates of labour induction and caesarean delivery, as well as associated with childhood obesity (26)(27)(28)(29)(30)(31) .…”
Section: Maternal Nutritional Status and Health Outcomesmentioning
confidence: 99%
“…Simultaneously, obesity is also prevalent in low-and middle-income countries and high-income countries, particularly among economically poor populations (22)(23)(24)(25) . Maternal obesity is associated with serious adverse pregnancy outcomes including early pregnancy loss, preterm birth, stillbirth, gestational diabetes, pre-eclampsia and other hypertensive disorders, higher rates of labour induction and caesarean delivery, as well as associated with childhood obesity (26)(27)(28)(29)(30)(31) .…”
Section: Maternal Nutritional Status and Health Outcomesmentioning
confidence: 99%
“…Among women of childbearing age, overweight and obesity have been associated with increased risk of non-communicable diseases (NCDs), pregnancy complications, caesarean section births, adverse birth outcomes, and infant mortality [8][9][10][11]. A recent study conducted in Tanzania reported associations between maternal overweight and increased risk of intrapartum obstetric complications and caesarean section births [12]. Furthermore, offspring of obese mothers have had up to 29% increased risk of hospital admission from cardiovascular disease and 35% increased risk of premature death in adulthood compared to offspring of normal BMI mothers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were conducted in Nigeria (6/17) [39][40][41][42][43][44]; and South Africa (3/17) [45][46][47] (Table 3). Twelve of the included studies were conducted either in tertiary health centres or maternity clinics [10,[39][40][41][42][43]45,46,[48][49][50][51]; while the other 5 studies were conducted in community or neighbourhood settings [38,44,47,52,53].…”
Section: Study Settingmentioning
confidence: 99%